Severe Distortion of the Apparent Resistivity Induced by the Super Geomagnetic Storm in May 2024 - Zhang, Xin; Xie, Tao; Ye, Qing; Yan, Liangjun; Wu, Xiaoping (Geophysical research letters, 2025)
The potential hazard of geomagnetically induced current (GIC) in metallic pipelines caused by space weather events is a widely discussed topic. On 10–11 May 2024, a super geomagnetic storm with Kp = 9 comparable to the Halloween event in 2003 occurred. The storm induced GIC caused severe distortion in apparent resistivity is a novel phenomenon. Here, we studied an apparent resistivity observation network of China, which was severely affected by the GIC. The impact reached over 15 times the static daily variation, inducing the apparent resistivity values to be significantly distorted, with 35 of 70 stations observing resistivity changes over 1%. Additionally, some stereo observations had significant responses and appeared time‐delay pattern reaching 24 hr. The induced polarization effect may involve and release the charges slowly, then delay the response pattern of apparent resistivity under the super storm. Effectively it is the first academic report of the GIC effect in apparent resistivity. Plain Language Summary A super geomagnetic storm with Kp = 9 occurred on Mother's Day in May 2024. During and after the super storm, the geoelectric field and apparent resistivity in China observed the influence of geomagnetic storm induced current (GIC), accompanied by synchronous time‐delayed response after the storm. We focus on how to understand the apparent resistivity response during the super storm. The findings show that the super storm induced a severe distortion of the apparent resistivity in mid‐latitude through the GIC in layers, and the induced polarization effect may delay the response pattern of apparent resistivity. This result is meaningful for the electromagnetic sounding to mislead interprets while space weather events onset. Key Points The super storm induced severe distortion of apparent resistivity in mid‐latitude through its geomagnetic storm induced current hazards The change of apparent resistivity observed below 100 m underground is more significant compared to that on the surface The induced polarization effect in layers delays the changing pattern of apparent resistivity under the super storm loading